Effect of processing on micronutrient content of chips produced from some plantain and banana hybrids - Adeniji, T.A.; Tenkouano, A. (International Society for Horticultural Science, 2007)
Introduction. Chips or crisps are the most important foods usually fried; they are presented in the form of thin discs (chips) or sometimes in the form of sticks (French fries). Materials and methods. Chips were prepared starting from pulp samples resulting from five hybrids of plantain and banana newly released in Nigeria and from a local cultivar used as reference. The iron, zinc and pro-vitamin A contents were investigated in the chips to unveil their micronutrient content. Results and discussion. The results showed that there was no significant difference (p < 0.05) in the iron content of the chips produced from the new plantain and banana hybrids, while a significant difference (p < 0.05) existed in both zinc and total carotenoid contents of the hybrids. Chips made from BITA 3, a hybrid cooking banana, could contribute 2.61 retinol equivalent (RE)e [1 (RE)e = 6 µg β-carotene (precursor of vitamin A)] daily, if a small packet of chips (45 g) is consumed, based on the Recommended Daily Dietary Allowance. A 45-g packet of chips made from PITA 26 can contribute 14.6% and 20.1% of the daily requirements of zinc per day, and 30.1% and 22.3% of the requirements of iron per day, for a man and a woman, respectively. Conclusions. The new plantain and banana hybrids may therefore significantly participate in a food strategy aiming at combating the lack of micronutrients in the sub-Saharan African diet.